PENGARUH HASIL PEMBELAJARAN AL-QUR’AN DI PENDIDIKAN NON FORMAL TERHADAP PRESTASI BELAJAR QUR’AN HADITS SISWA KELAS VII MTs AL-AZHAR SEMPU - Imam Mashuri; Ahmad Aziz Fanani; Siti Mu’awanah (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to find out how much influence between the results of Qur'anic learning in non-formal education on the learning achievements of Qur'an Hadith students of grade VII at MTs Al-Azhar Sempu. This research is a quantitative study conducted at MTs Al-Azhar Sempu. Data collection methods in using observation instruments, tests, and documentation. Data analysis techniques with simple linear Regression data analysis techniques. The results showed that there was a significant positive influence between the learning outcomes of the Qur'an in non-formal education on the achievements of the Qur'an Hadith in schools.